Multi-pathogen serological survey of migratory caribou herds: A snapshot in time - Carlsson, Anja M.; Curry, Patricia S.; Elkin, Brett T.; Russell, Donald E.; Veitch, Alasdair M.; Branigan, Marsha; Campbell, Mitch; Croft, Bruno; Cuyler, Christine; Côté, Steeve D.; Leclerc, Lise-Marie; Tryland, Morten; et al. (PLOS ONE, 2019)
Pathogens can impact host survival, fecundity, and population dynamics even when no obvious disease is observed. Few baseline data on pathogen prevalence and diversity of caribou are available, which hampers our ability to track changes over time and evaluate impacts on caribou health. Archived blood samples collected from ten migratory caribou herds in Canada and two in Greenland were used to test for exposure to pathogens that have the potential to effect population productivity, are zoonotic or are emerging. Relationships between seroprevalence and individual, population, and other health parameters were also examined. For adult caribou, the highest overall seroprevalence was for alphaherpesvirus (49%, n = 722), pestivirus (49%, n = 572) and Neospora caninum (27%, n = 452). Lower seroprevalence was found for parainfluenza virus type 3 (9%, n = 708), Brucella suis (2%, n = 758), and Toxoplasma gondii (2%, n = 706). No animal tested positive for antibodies against West Nile virus (n = 418) or bovine respiratory syncytial virus (n = 417). This extensive multi-pathogen survey of migratory caribou herds provides evidence that caribou are exposed to pathogens that may have impacts on herd health and revealed potential interactions between pathogens as well as geographical differences in pathogen exposure that could be linked to the bio-geographical history of caribou. Caribou are a keystone species and the socio-economic cornerstone of many indigenous cultures across the North. The results from this study highlight the urgent need for a better understanding of pathogen diversity and the impact of pathogens on caribou health.